Pengembangan Media Pembelajaran Scrapbook untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam di SDN 112 Kabupaten Seluma - Juwita Melati Sukma; Riswanto; Rini Pupitasari (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to develop a learning media in the form of a scrapbook to enhance students' learning motivation in the Islamic Religious Education subject at SDN 112, Seluma Regency. The method used is Research and Development (R&D) with the Four-D (4-D) model, which consists of four main stages: Define, Design, Develop, and Disseminate. The research subjects were fifth-grade students of SDN 112 Seluma, and data were collected through observation, interviews, questionnaires, and documentation. The results show that: (1) the validity of the scrapbook media based on expert validation was 85% for media experts, 81% for material experts, and 88% for language experts, categorized as very valid; (2) the practicality of the scrapbook learning media based on student responses averaged 93%, categorized as very practical; and (3) students' interest in the scrapbook learning media averaged 89%, categorized as very high. In conclusion, the scrapbook learning media can improve the learning motivation of fifth-grade students at SDN 112 Seluma. Keywords: Islamic Religious Education, Learning Media, Learning Motivation, Scrapbook, Elementary School